An Overview on Case Internet Addiction in Early Childhood’s Perspective - Nurhafizah Nurhafizah; Wilma Rahmah Hidayati (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This article was written based on research that aims to describe the level of internet addiction in early childhood in TK Nagari Lima Kaum with quantitative descriptive research methods. The novelty in this study is to find out data on the level of internet addiction in early childhood’s perspective in Nagari Lima, where the topic of this research has not been studied by other researchers. The results showed that the level of internet use in AUD in Nagari Lima Kaum was 23 respondents in the high category, 7 respondents in the medium category, 3 respondents in low category, and 2 of the respondents in the very low category. This can be a record of parents and the surrounding environment in providing supervision to children when using the internet and gadgets to avoid internet addiction. Limiting internet usage time for children and providing time to play together can be one solution that can be given by parents. The conclusion of this study is that the level of internet addiction in Nagari Lima Kaum is in the high category.